Antibiotic Combinations with Daptomycin for Treatment of Staphylococcus aureus Infections - Nadrah, Kristina (Hindawi Publishing Corporation, 2011)
Daptomycin is a lipopeptide antibiotic with a unique mechanism of action on Gram-positive bacteria. It is approved for treatment of skin and soft-tissue infections with Gram-positive bacteria, bacteraemia and right-sided infective endocarditis caused by Staphylococcus aureus. Diminishing susceptibility of S. aureus to daptomycin during treatment of complicated infections and clinical failure have been described. Combinations of daptomycin with other antibiotics including gentamicin, rifampin, beta-lactams, trimethoprim/sulfamethoxazole (TMP-SMX), or clarithromycin present a new approach for therapy. In vitro and animal studies have shown that such combinations may, in some cases, be superior to daptomycin monotherapy. In this paper we focus on the antibiotic combinations for complicated S. aureus infections.